A brain drain in Russian agriculture? Migration sentiments among skilled Russian rural youth - Vasyl Kvartiuk; Martin Petrick; Miroslava Bavorova; Zuzana Bednaříková; Elena Ponkina (Europe-Asia Studies, 2020)
Urbanisation and the ageing of the rural population contribute to shortages of skilled workers in agricultural sectors worldwide. Migration may potentially alleviate these shortages. This study explores individual decision-making by skilled Russian rural youth with respect to migration, paying special attention to values and attitudes. Using qualitative and quantitative data, we identify major factors that may influence intentions to move abroad. Apart from income differentials, we find that social ties, individual values and attitudes are associated with migration intentions. Agricultural students unwilling to work in agriculture and who dislike the rural lifestyle tend to be motivated to migrate abroad in search of an alternative.
Keywords: 330